2023
DOI: 10.1017/s1355617723000206
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness is associated with mentalizing and emotion recognition abilities in schizophrenia, but only in a cluster of patients with social cognitive deficits

Abstract: Objective: Loneliness is a concern for patients with schizophrenia. However, the correlates of loneliness in patients with schizophrenia are unclear; thus, the aim of the study is to investigate neuro- and social cognitive mechanisms associated with loneliness in individuals with schizophrenia. Method: Data from clinical, neurocognitive, and social cognitive assessments were pooled from two cross-national samples (Poland/USA) to examine potential predictors of loneliness in 147 patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Individuals experiencing higher scores on loneliness were more likely to have poor mentalizing compared to people feeling satisfied with their social relationships. Previous studies have found negative correlation between loneliness and mentalizing only in patients suffering from schizophrenia [ 47 ]. The present study, conducted on non-clinical population, suggests that this relationship exists also among individuals from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals experiencing higher scores on loneliness were more likely to have poor mentalizing compared to people feeling satisfied with their social relationships. Previous studies have found negative correlation between loneliness and mentalizing only in patients suffering from schizophrenia [ 47 ]. The present study, conducted on non-clinical population, suggests that this relationship exists also among individuals from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…predominant 'focus on social cues indicating social isolation') on various levels of social information processing. Indeed, loneliness has been associated with more pronounced social cognitive bias (Okruszek et al, 2021(Okruszek et al, , 2023Qualter et al, 2013), attentional threat bias (Wei et al, 2020), and distrust (Lieberz et al, 2021) in reaction to social stimuli. Thus, investigating the effects of loneliness on negative appraisals of one's social company might be crucial for understanding its potential pathways towards psychopathology.…”
Section: Effects Of Trait Lonelinessmentioning
confidence: 99%
“…Notably, many studies examining the sensitivity to social threat in lonely individuals (LI) were conducted in laboratory settings and with the use of questionnaire measures (Lieberz et al, 2021;Okruszek et al, 2021Okruszek et al, , 2023Qualter et al, 2013;Wei et al, 2020). At the same time, it has been increasingly recognised that research in the field of mental health requires investigation of experience in naturalistic settings (Myin-Germeys et al, 2018), especially in social contexts (Redcay & Schilbach, 2019).…”
Section: Effects Of Momentary Lonelinessmentioning
confidence: 99%
See 1 more Smart Citation